Fiscal Dynamics and Financial Capacity in South Sulawesi Province - Rahman Bato, Aulia; Bulutoding, Lince; Sudarwinti, Sudarwinti (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2025)
This study examines the effects of the flypaper effect, fiscal stress, and tax effort on the financial capacity of South Sulawesi Province over the period 2002 to 2024 using the VECM method. In the short term, none of the identified factors exerts a significant influence on fiscal capacity. However, in the long term, the flypaper effect and fiscal stress are found to negatively affect financial capacity, whereas tax effort is found to have a positive effect. The flypaper effect indicates dependence on central transfers, reducing fiscal efficiency. Fiscal stress arises from imbalances that weaken capacity, while tax effort enhances fiscal autonomy by maximizing local revenue. These findings emphasize the importance of reducing fiscal dependence, improving spending efficiency, and promoting good governance to strengthen financial sustainability. The quality of institutions and governance also plays a crucial role in determining the success of fiscal policy at the regional level